O036 Does Cxbladder accurately exclude bladder urothelial cell malignancy on diagnostic and surveillance cystoscopy? a prospective multi-centre study. (22nd July 2022) - Narroway, H; Kovacic, J
Abstract: Introduction and Objectives: Health systems incur significant costs from bladder cancer. Diagnostic and surveillance protocols are intensive. Urine cytology and Computed tomography (CT) have low sensitivity as screening and surveillance tools. Cxbladder is a non-invasive urinary biomarker approved for use in Australia, with high reported sensitivity in bladder cancer detection. The purpose of this study was to determine the accuracy of Cxbladder as a screening and surveillance tool in patients with suspected and established bladder cancer, respectively. Methods: A prospective trial (88 participants) was performed at Gosford and North Gosford Hospitals (New South Wales, Australia). Inclusion criteria were: patients undergoing investigation for macroscopic haematuria or bladder cancer surveillance. Patients were asked to perform a Cxbladder test prior to either flexible or rigid cystoscopy. Exclusion criteria were: patients aged < 18 years, or patients that had undergone transurethral resection of the bladder within five months. Testing kits were supplied at no cost by Pacific Edge Ltd. Cxbladder results were then compared with cystoscopic findings, the prevailing gold-standard for bladder cancer diagnosis. Results: Sensitivity and specificity of Cxbladder for detection of bladder cancer were 76.5% and 45.1% respectively. Positive and negative predictive values (PPV/NPV) were 31.7% and 85% respectively. False negative cases comprised low-grade papillary tumours only. Cxbladder had 100% NPV in detection of high-risk bladder cancer. Conclusion: There is evidence to support Cxbladder as a screening tool in the detection of high-risk bladder cancer. Further studies involving larger populations are required to validate its accuracy. Take-home message: The purpose of this study was to determine the accuracy of Cxbladder as a screening and surveillance tool in patients with suspected and established bladder cancer, respectively. Sensitivity and specificity of Cxbladder for detection of bladder cancer were 76.5% and 45.1% respectively, whilst a 100% negative predictive value was obtained in detection of high-risk bladder cancer.